Research Into Mental Health Prediction of Community Workers Involved in the Prevention of COVID-19 Epidemic Based on Cloud Model - Huang, Jialing (Frontiers in Public Health, 2022)
In order to explain the psychological state of COVID-19 pandemic control community staffs, provide them with psychological counseling guidance and predict their psychological well-being status, the cloud model was constructed in this study. Firstly, the data collection method of psychological well-being was constructed. Secondly, the definition of the cloud was given, the digital characteristics of the cloud were analyzed, and the cloud theory model was constructed. Thirdly, the psychological well-being prediction model for the pandemic control community staffs was established based on the cloud theory, and corresponding procedures for the proposed algorithm was designed. Finally, a community was selected as the research object for the prediction analysis of psychological well-being. The research results prove that the proposed model can effectively predict the psychological well-being status of pandemic control community staffs.